Effekt av ras och säsong på nötkreaturs avbetningsgrad av konkurrenskraftiga betesmarksväxter - Bertilsson, Jannicke (SLU/Dept. of Animal Environment and Health (until 231231), 2006)
Grasslands which have been actively managed for a long time and which in modern times have not been subject to cultivation such as fertilization are called semi-natural grasslands. These rare and species-rich areas hold an ecological, biological and historical value and if the management stops these areas will likely diminish. More effective agricultural systems and a declining number of grazing animals have in Sweden, among other countries, made semi-natural grasslands less valuable as foraging areas. Shrubs and fast growing plants rapidly colonize abandoned semi-natural grasslands, threatening biodiversity.